Odpowiedzi

2010-03-03T11:36:06+01:00
A) -2(2x-1)=x/3
-4x +2 = x/3





b)2/5(3-x)=-2
0,4(3-x)=-2
1,2-0,4x=-2
-0,4x = -2-1,2
-0,4x = -3,2 /(-0,4)
x = 8

c) 3/4 (2-3x)= -6
0,75(2-3x) =-6
1,5 -2,25x = -6
-2,25x = -6 - 1/5
-2,25x = -4,5/(-2,25)
x = 2
d) 1/5 (x-3)=9-x
0,2x- 0,6= 9-x
0,2x +x = 9+0,6
1,2x = 9,6/1,2
x = 8

e)
2010-03-03T11:42:27+01:00
A) -2 (2x - 1) = x/3
-4x+4=x/3
-4x-x/3=-4
-12x-x=-12
-13x=-12
x=12/13
b) 2/5 (3 -x) = -2
6/5-2/5x=-2
-2/5x=-2-6/5
-2/5x=-26/5
x=8
c) 3/4 (2 - 3x) = -6
6/4-9/4x=-6
-9/4x=-6-6/4
-9/4x=-66/4
x=-30/4*(-4/9)
x=3 1/3
d)1/5 (x - 3) = 9 - x
1,5x-4,5=9-x
1,5x+x=8+4,5
2,5x=13,5
x=5,4
e) 0.6 + x /2 = x +1
x/2-x=1-0,6
x-2x=2-1,2
-x=0,8
x=-0,8